Small cell carcinoma of the urinary bladder treated with neo-adjuvant cp chemotherapy (CPT-11 and CDDP) a case report - Funahashi, Makoto (Hinyokika kiyo. Acta urologica Japonica, 2007)
We report a cases of primary small cell carcinoma of the urinary bladder. A 68-year-old man was referred to our hospital because of asymptomatic gross hematuria. Cystoscopy showed a solid tumor on the dome of the urinary bladder. Pelvic magnetic resonance imaging (MRI) revealed a mass lesion with extravesical extention, and computed tomography(CT) scan and bone scintigraphy showed no distant metastasis. Transurethral resection of the bladder tumor (TUR-BT) was performed. Histopathological findings of the specimen showed small cell carcinoma (> pT2), with transitional cell carcinoma (TCC), grade 2-3. We performed one course of neoadjuvant CP chemotherapy using Irinotecan (CPT-11) and Cisplatin (CDDP), followed by radical cystectomy. Histopathological finding of the specimen showed no evidence of malignancy. We performed one more course of adjuvant CP chemotherapy. He has been free of disease 7 months after operation